Interdisciplinary teamwork for chest tube insertion and management: an integrative review - Ghazali, Daniel; Ilha-Schuelter, Patricia; Barbosa, Sarah; Truchot, Jennifer; Ceccaldi, Pierre; Tourinho, Francis; Plaisance, Patrick (Anestezjologia Intensywna Terapia, 2021)
Thoracostomy requires interdisciplinary teamwork. Even though thoracic drainage is a technical surgical procedure, nurses play an important role with major responsibilities during the procedure. This literature review aimed to identify articles related to the interdisciplinary management of thoracostomy. An integrative literature analysis between 2012 and 2019 with a qualitative approach was conducted. An analysis of articles written in English, French, Portuguese, and Spanish was conducted. A search of the PubMed and SCIELO databases was performed using combinations of the terms “Chest Tube; Nursing; Care; Drainage; Insertion”. The search terms were included in 11,277 articles. After excluding articles that did not meet the objective of our study, 475 abstracts were analysed. Finally, 19 articles were selected with content focused on nursing care, content related to surgical procedures, and interdisciplinary content. Themes included the following: description of the procedure, interdisciplinary action, quality of the procedure, use of protocols for patient safety, and new technologies. In conclusion, interdisciplinary courses should be encouraged to improve interprofessional teamwork organization. Notwithstanding all these publications, the literature was fragmented into disciplines and isolated analyses. Each medical or nursing discipline addressed the aspects that pertain to its own responsibilities in the execution of the procedure. This review highlighted the need to develop interdisciplinary research and brought a source of rich information that can instrumentalize the creation of optimized processes for the interdisciplinary chest tube insertion.